Health-related quality of life, psychosocial strains, and coping in parents of children with chronic renal failure - Wiedebusch, Silvia; Konrad, Martin; Foppe, Helmut; Reichwald-Klugger, Evelyn; Schaefer, Franz; Schreiber, Vera; Muthny, Fritz A. (Pediatric nephrology, 2010)
Health-related quality of life (HRQOL) in parents of children suffering from renal disease is often diminished by the illness burden experienced in daily life and by unfavorable ways of coping. Our aim was to examine the relationship between psychosocial strains perceived by parents, their ways of coping, and HRQOL. In an anonymous cross-sectional study, parents completed a questionnaire concerning psychosocial strains, coping strategies, and HRQOL, as well as sociodemographic and illness parameters. Study participants were recruited in two outpatient dialysis centers. Participating in the study were 195 parents (105 mothers, 90 fathers; age 43 ± 8 years; representing 108 families) of children suffering from renal disease (age 12 ± 5 years). Parents of children with chronic renal failure reported moderate HRQOL with parents of children undergoing dialysis experiencing more limitations in quality of life than parents of children living with a kidney graft and parents of children undergoing conservative treatment. Mothers experienced lower HRQOL and higher psychosocial strains than fathers. HRQOL was predicted by the coping strategies “focusing on child” (β = -0.25), “improving marital relationship” (β = 0.24), “seeking social support” (β = -0.22) and “self-acceptation and growth” (β =0 .19) as well as parents′ perceived limitation by illness in daily life (β = -0.15; explained variance 57%). In the comprehensive care for families with a child suffering from a renal disease, screening for psychosocial strains and ways of coping, along with applying interventions to strengthen adaptive coping strategies, may be a preventative means of improving parents′ quality of life.
Gesehen am 29.01.2024